A Hypothesis for Examining Skeletal Muscle Biopsy-Derived Sarcolemmal nNOSμ as Surrogate for Enteric nNOSα Function - Chaudhury, Arun (Frontiers in Medicine, 2015)
The pathophysiology of gastrointestinal motility disorders is controversial and largely unresolved. This provokes empiric approaches to patient management of these so-called functional gastrointestinal disorders (FGIDs). Preliminary evidence demonstrate that defects in nNOS expression and function, the enzyme that synthesizes nitric oxide (NO), the key inhibitory neurotransmitter mediating mechano-electrical smooth muscle relaxation, is the major pathophysiological basis for sluggishness of oro-aboral transit of luminal contents. This opinion is an ansatz of the potential of skeletal muscle biopsy and examining sarcolemmal nNOSµ to provide complementary insights regarding nNOSα expression, localization and function within enteric nerve terminals, the site of stimulated de novo NO synthesis. The main basis of this thesis is two-folds: (a) the molecular similarity of the structures of nNOS α and µ, similar mechanisms of localizations to “active zones” of nitrergic synthesis and same mechanisms of electron transfers during NO synthesis (b) pragmatic difficulty to routinely obtain full-thickness biopsies of gastrointestinal tract, even in patients presenting with the most recalcitrant manifestations of stasis and delayed transit of lu